“This is not what god intended”: attitudes toward adoption by same-sex couples in Ecuador (2022)
Introduction: In Ecuador, adoption is limited to heterosexual couples and information on attitudes toward same-sex couples who intend to become parents following this pathway is scarce. This study aimed to identify the beliefs of a sample of 319 cisgender people in Ecuador regarding the adoption of children by same-sex couples and explore the reasons why they consider it is appropriate or not for lesbian and gay (LG) couples to adopt children. Methods: Between May and October 2019, participants responded quantitative and qualitative questions after reading a vignette about a couple interested in adopting a child. Participants were randomly presented with one out of three versions of the vignette based on the couples’ sexual orientation (L,G, heterosexual). Descriptive, correlational statistics and analysis of variance were used to conduct quantitative analyses. Qualitative responses were analyzed using thematic and content analysis. Results: Results indicate favorability toward adoption by all couples in general. However, people showed the highest concerns about adoption by LG couples. Qualitative answers indicate the existence of nine types of arguments used by participants to explain their position in favor or against adoption by same-sex couples. Conclusion: Some are problematic since they are rooted in prejudiced ideas about heterosexual people’s superiority regarding their capacities to create emotionally nurturing environments. Policy Implications: Providing information regarding LG parenting might be a way of achieving legislative changes that might, in turn, promote social change by providing a legal platform for same-sex couples to achieve parenthood